The effect of deep breathing exercises on anxiety levels among students approaching school examinations - Sutrisno Sutrisno; Desinta Aldefintania Sasti; Anik Suwarni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Anxiety is an emotional response commonly experienced by students before school examinations and may affect physical, cognitive, and emotional aspects. High levels of anxiety can decrease concentration and academic performance. One non-pharmacological method that can be used to reduce anxiety is deep breathing exercise Purpose: To determine the effect of deep breathing exercise on the anxiety level of tenth-grade students to school examinations. Method: A pre-experimental design with a one-group pretest-posttest design and a total sampling technique. Anxiety levels were measured using the STAI-S questionnaire before and after the deep breathing exercise intervention. Data were analyzed using paired sample t-tests, both univariately to assess the distribution of anxiety levels and bivariate to analyze the effect of the intervention. Results: There was a decrease in anxiety levels after being given deep breathing exercises with a difference in average values ​​of 39.83. Statistical analysis obtained a P-Value of 0.001 (p < 0.05) indicating that deep breathing exercises had a significant effect on reducing students' anxiety levels before school exams. Conclusion: Deep breathing exercise is effective as an independent intervention to reduce students’ anxiety levels prior to school examinations. Keywords: Anxiety Level; Deep Breathing Exercise; Students, School Examination.